Respuesta :
Answer:
x = 6
y = 3
Explanation:
The second equation given is:
x - y = 3
This can be rewritten as:
x = y + 3 .........> I
The first given equation is:
2x + y = 15 ..........> II
Substitute with I in II and solve for y as follows:
2x + y = 15
2(y+3) + y = 15
2y + 6 + y = 15
3y = 15 - 6
3y = 9
y = 9/3 = 3
Now, substitute with the value of the y in I to get x as follows:
x = y + 3
x = 3 + 3
x = 6
Hope this helps :)
x = 6
y = 3
Explanation:
The second equation given is:
x - y = 3
This can be rewritten as:
x = y + 3 .........> I
The first given equation is:
2x + y = 15 ..........> II
Substitute with I in II and solve for y as follows:
2x + y = 15
2(y+3) + y = 15
2y + 6 + y = 15
3y = 15 - 6
3y = 9
y = 9/3 = 3
Now, substitute with the value of the y in I to get x as follows:
x = y + 3
x = 3 + 3
x = 6
Hope this helps :)